Cedar Cove : 16 Lighthouse Road - Book 1 - Macomber, Debbie (Toronto, Ontario, Canada : Mira, 2023)
Family court judge Olivia Lockhart becomes front page news when she refuses to grant a divorce to a naval officer and his wife after the the death of their baby, and discovers the lives of her family to be increasingly complex.
Keywords: Women judges -- Fiction; Cedar Cove (Wash. : Imaginary place) -- Fiction; Washington (State) -- Fiction; Romance fiction